Energy efficiency for reinforcing steel activities in the construction of a business complex in Mexico - Javier Esquer; Jorge Rafael Morales-Sau; Luis E. Velázquez; Juana Alvarado-Ibarra; Nora Elba Munguia (Economic and Environmental Studies (E&ES), 2017)
Much of the energy used in the world is associated with the construction sector, and one of the ways to reduce that energy consumption is to do each constructive process in an energetically efficient way. The aim of this paper is to present results from an energy efficiency program in the construction of a business complex in Hermosillo, Mexico, particularly in the processes of reinforcing steel activities (rebar). Results reveal that appropriate use of equipment and the coordination between engineers and workers help to improve the energy efficiency during the construction phase also reducing material waste. Additionally, attaching the energy efficiency approach to the cleaner production framework is a complicated task due to energy inefficiencies are not easily identified and estimated. Since there is less energy consumption in construction process along the life cycle of buildings compared to operation activities, there is little evidence on energy efficiency studies in that part of the process. Therefore, this paper intends to provide experiences to construction experts in order to have better basis for decisions related to energy efficiency in this industry.
Keywords: Q40; Q49; L74; 330; Construction; energy efficiency; environment; sustainability; reinforcing steel; Mexico